Zur Morphologie und Biologie des Luzernemarienkäfers Subcoccinella vigintiquatuorpunctata L. (Coleoptera: Coccinellidae). - Tanasijevic, Nikola (Contributions to Entomology = Beiträge zur Entomologie, 1958)
Based upon studies during several years in different parts of Jugoslavia it was possible to extend the range of the hitherto insufficient knowledge on the morphology, anatomy, bionomy, and ecology of Subcoccinella vigintiquatuorpunctata L. This species injurious to cultivated plants (especially Papilionaceae) in contraposition to the most of the other predaceous Coccinellidae, is known from Jugoslavia in two generations, one of them hibernating as imago in the ground. There are published the results of investigations on morphology-anatomy (external characters, genitalia, alimentary canal etc.), bionomy (oviposition, development, nutrition, diapause etc.) as like as ecology (influence of temperature and moisture to bionomie data, sex rate, population ecology) of this species.